Love armored by God: the maintenance of loving coexistence by the market of Pentecostal couples’ meetings - Santos, James Washington Alves dos (2021)
This article has as its object of study the notion of Christian love and marriage. This happens through the dialogue of the Judeo-Christian tradition, inspired in its formation, by the biblical texts. By seeking to consider the intercultural arguments for showing, from the inside, the sociogenesis and configuration of the notions of love, marriage and hetero-normativity of current Brazilian Pentecostalism. This leads us not only to the delimitation of the object and its methodology, but to the implication that this theme is of paramount importance for the understanding of the Brazilian cultural reality, as seen in the defense of a specific model of love, marriage and family which instigates debates. After describing these notions, the analysis of problems such as male authority, the indissolubility of the matrimonial union and the practice of sexuality in view of reproducibility follows. It also implies in an attempt of finding the solution, either by the religious education or by couple´s meetings, to the real crises arising from these problems. This analysis is based on Norbert Elias’ theories (regarding the social configuration and the issue of socio-genesis).